Using sternal angle as anatomic landmark for right internal jugular vein catheterization in pediatrics. Issue 2 (7th October 2019) - Xu, Hui; Zhu, Xiaoqiu; Li, Jin; Yao, Yiyi; Guo, Mingyan; Yu, Taihui; Xiong, Xilin; Huang, Zhiquan; Miao, Liping; Lin, Daowei
Abstract : Background: Many formulas based on the patient's height, weight and/or age exist to determine central venous catheter (CVC) depth in children. However, this information is unavailable in some emergency conditions. Therefore, direct methods should be developed to guide catheter position in children. Methods: Eighty patients aged 1–10 y were enrolled from July 2015 to August 2016 and seventy‐five were completed; fifty were male, and twenty‐five were female. The exclusion criteria were inability to identify the sternal angle or failure to use the right internal jugular vein approach. The catheter was inserted using the right internal jugular vein approach, the distance from the skin puncture point to the midpoint of the sternal angle plane was measured, and the catheter tip was positioned to this distance minus 1 cm. Chest radiography were performed for those children after catheter insertion. The relative position between the catheter tip and carina was confirmed and the longitudinal distance from the catheter tip to the carina was calculated on radiographic images, and related complications were recorded. Results: All catheter tips were above the carina, and the average distance from the catheter tip to the carina was 9.8 mm. No patients experienced serious complications. Conclusion: The sternal angle is a useful and reliable anatomic landmark for guiding CVC position in children. Using this landmark, the catheter can be quickly and conveniently placed at a safety position in right internal jugular vein, especially in some emergency conditions.